Effect of Airflow Velocity on Pre-cooling Process of Pomegranate by Forced Cooling Air under Unsteady State Heat Transfer Condition - M. A Behaeen (Ferdowsi University of Mashhad, 2018)
Introduction Pomegranate (Punica grantum L.) is classified into the family of Punicaceae. One of the most influential factors in postharvest life and quality of horticultural products is temperature. In precooling, heat is reduced in fruit and vegetable after harvesting to prepare it quickly for transport and storage. Fikiin (1983), Dennis (1984) and Hass (1976) reported that cold air velocity is one of the effective factors in cooling vegetables and fruits. Determining the time-temperature profiles is an important step in cooling process of agricultural products. The objective of this study was the analysis of cooling rate in the center (arils) and outer layer (peel) of pomegranate and comparison of the two sections at different cold air velocities. These results are useful for designing and optimizing the precooling systems. Materials and Methods The pomegranate variety was Rabab (thick peel) and the experiments were performed on arils (center) and peel (outer layer) of a pomegranate. The velocities of 0.5, 1 and 1.3 m s-1 were selected for testing. To perform the research, the cooling instrument was designed and built at Department of Biosystems Engineering of Tabriz University, Tabriz, Iran. In each experiment six pt100 temperature sensors was used in a single pomegranate. The cooling of pomegranate was continued until the central temperature reached to 10°C and then the instrument turned off. The average of air and product temperatures was 7.2 and 22.2°C, respectively. The following parameters were measured to analyze the process of precooling: a) Dimensionless temperature (θ), b) Cooling coefficient (C), c) Lag factor (J), d) Half-cooling time (H), e) Seven-eighths cooling time (S), f) Cooling heterogeneity, g) Fruit mass loss, h) Instantaneous cooling rate, and i) convective heat transfer coefficient. Results and Discussion At any air velocity, with increasing the radius from center to outer layer, the lag factor decreased and cooling coefficient increased. Also, half-cooling time and seven-eighths cooling time reduced and so cooling rate enhanced. Thus, despite a reduction lag factor, due to a significant increase in cooling coefficient, half and seven-eighths cooling declined. Dimensionless temperature, θ, less than 0.2 and 0.1 in the center and peel and at different velocities had little impact on the rate of cooling in pomegranate. The difference in primary cooling time (0-500 sec) and in high lag factor (greater than 1) occurred, which represents an internal resistance of heat transfer in fruit against the airflow. Cooling the center of pomegranate starts with time delay which causes the beginning of the cooling curve becomes flat. Seven-eighths cooling time is the part of half-cooling time. The range of S was 2.5-3.5H in the present study. At first, cooling heterogeneity at 0.5 m s-1 was low in the center and peel of pomegranate and then with increasing the velocity up to 1 m s-1, it enhanced and again decreased at 1.3 m s-1. After a period of cooling (5000 sec), almost layers of pomegranate reached the same temperature and so heterogeneity reduced. The maximum instantaneous cooling rate was 8.09 × 10-4 ºC s-1 at 1.3 m s-1 in the center of pomegranate. By increasing the airflow velocity from 0.5 to 1.3 m s-1, the convective heat transfer coefficient increased from 11.05 to 17.51 W m-2 K-1. Therefore, the velocity of cold air is an important factor in variation of convective heat transfer coefficient. Conclusions Cooling efficiency is evaluated based on rapid and uniformity of cooling. Cooling curves against time reduced exponentially at the different airflow velocities in the center (aril) and outer layer (peel) of pomegranate. By increasing the air flow velocity, half and seven-eighths cooling time reduced and cooling rate increased that showed direct impact of this variable. The main reason was the variation of convective heat transfer coefficient. The lowest level of uniformity obtained at the highest velocity (1.3 m s-1), which made more uniform temperature distribution in the fruit. The results showed that applied method in this experiment could be used for the fruits which are similar to sphere and could explain the unsteady heat transfer without complex calculations in the cooling process. Based on the results of this research, the airflow velocity of 1.3 m s-1 is recommended for forced air precooling operations of pomegranate.